Establishing a CRISPR/Cas9 genome editing framework in pigeonpea (Cajanus cajan L.) by targeting phytoene desaturase (PDS) gene disruption - Kameshwaran Senthil; Maniraj Rathinam; Manisha Parashar; Narasimham Dokka; Shaily Tyagi; Vandana Mathur; Sandhya Sharma; Kishor Gaikwad; Ramcharan Bhattacharya; Rohini Sreevathsa (Journal of Genetic Engineering and Biotechnology)
Pigeonpea is an important legume valued for its high nutritional, agricultural, and economic significance in the Asian subcontinent. Despite its potential for high yield, productivity remains stagnant due to several abiotic and biotic stresses. To mitigate these challenges, biotechnological interventions like genome editing offer promising solutions. Towards this, developing a species-specific editing toolkit is crucial for recalcitrant species like pigeonpea. In this study, we established a CRISPR/Cas9 genome editing system targeting the phytoene desaturase (PDS) gene. We developed pigeonpea-compatible vector components, including the CcU6_7.1 promoter and an amenable Cas9 gene driven by the potato ubiquitin promoter, creating a pigeonpea-specific CRISPR/Cas9 binary vector (PP_CRISPR_pCAMBIA2301). The system was validated by Agrobacterium tumefaciens-mediated apical meristem-targeted in planta and in vitro embryonic axis explant transformations, with gene knockout confirmed by albino/bleached phenotypes. Editing efficiencies were 8.80% and 9.16% in the in planta and in vitro transformations respectively. While PCR analysis confirmed T-DNA integration, sequence analysis identified PDS gene mutations. Stability of the phenotype was demonstrated in T1 generation plants of in planta transformation-developed mutants. This system may support functional genomics studies and trait improvement in pigeonpea and other legumes.